Tedania (Porifera: Demospongiae: Poecilosclerida) from the Mexican Pacific with the description of two new species. Issue 19 (27th May 2018) - Aguilar-Camacho, Jose Maria; Carballo, Jose Luis; Cruz-Barraza, Jose Antonio
Abstract : Two new species of Tedania (Porifera: Demospongiae: Poecilosclerida) are described from the Mexican Pacific. Tedania ( Tedania ) tropicalis sp. nov. is an encrusting to massive sponge having ectosomal tylotes with microspined heads, choanosomal styles and onychaetes. Tedania ( Tedania ) fulvum sp. nov. is a thinly encrusting sponge having ectosomal tylotes with smooth heads, choanosomal styles and onychaetes. Tables for all the Tedania (subgenera Tedania and Tedaniopsis ) and Trachytedania species described worldwide are included. We suggest that species of Tedania and Trachytedania bearing ectosomal diactinal spicules (excluding Tedania ( Stylotedania )) can be separated in two main groups: those having choanosomal monactinal spicules and those with choanosomal diactinal spicules. www.zoobank.org/urn:lsid:zoobank.org:pub:5B212DC3-3827-44D5-8E63-3E652BCB29E6